Integrasi Psikologi Trading, Manajemen Keuangan, dan Manajemen Risiko dalam Pendidikan Finansial: Pendekatan Teoritis untuk Optimalisasi Hasil Perdagangan Jangka Panjang - Siti Harwianti Santoso; Surya Danang; Fitayantri Tamau; Zerah Elisa Derek (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine long-term trading performance in financial markets by focusing on the role of risk management, financial management, and trading psychology as the main objects of analysis. The research problem arises from the limitations of technical and fundamental analysis in explaining sustainable trading performance, highlighting the need for an integrative perspective grounded in behavioral finance and management theory. The proposed method employs a conceptual approach through a systematic synthesis of recent empirical and theoretical studies published between 2020 and 2025. The findings indicate that structured risk mitigation, disciplined capital management, and effective emotional control in decision-making are closely interconnected and jointly contribute to improving the resilience and consistency of trading outcomes. The synthesis of the main ideas emphasizes that behavioral and managerial factors play a critical role in sustaining long-term trading strategies. In conclusion, the integration of risk management, financial management, and trading psychology constitutes a fundamental framework for achieving sustainable and adaptive trading performance in dynamic financial markets.